Scoping review study to identify how communities in the USA, Australia, New Zealand and Canada use quality improvement (QI) approaches to address community health and well-being - Rohit Ramaswamy; Tara Carr; Mallory Wolfe Turner (BMJ Open)
Introduction Both US and global communities lag on key health indicators. There has been limited progress in building capacity to improve health beyond the healthcare field. Yet, communities also need to engage in health improvement initiatives. A substantial body of literature describes standards and core components for quality improvement (QI) approaches in clinical settings. This study aims to determine how communities in the USA, Australia, New Zealand and Canada use QI approaches for health and well-being improvement and how such approaches compare to those in clinical settings.Methods and analysis We developed a study protocol based on scoping review framework by Arksey and O’Malley, methodological advancements for scoping studies (Levac et al) and other published protocols. We developed research questions in an iterative process and used the Population, Intervention, Comparison, Outcomes strategy to determine eligibility criteria. Electronic databases deemed appropriate (Web of Science, Scopus, and Proquest Health Management) will be searched for studies that meet inclusion criteria. References of included studies will be included when relevant. Two reviewers will independently screen all abstracts and full-text studies for inclusion. A third reviewer will adjudicate disagreements that arise. An instrument will be developed to extract data from included studies. Quantitative and qualitative results will be reported.Ethics and dissemination We developed this protocol to systematically conduct a scoping review of how US communities use QI approaches to address community health and well-being. Results will benefit multiple stakeholders by informing how to better support, design and evaluate community well-being improvement interventions. Results will be distributed through peer-reviewed journals, conferences, presentations and a public health graduate course.